Short interspersed repetitive elements (SINEs) from the cichlid fish, Oreochromis niloticus, and their chromosomal localization by fluorescent in situ hybridization - Oliveira, Claudio [UNESP]; Wang, Yimin; Bryden, Louis J.; Wright, Jonathan M. (Firenze University Press, 2003)
In the present study, we describe the cloning and characterization of a new SINE-like element from O. niloticus (ROn-2) and show the distribution of this SINE and a previously isolated SINE, ROn-1, in the chromosomes of O. niloticus. The ROn-2 element is 359 base pairs (bp) in length, contains short direct terminal repeats, a tRNA-related region similar to tRNA Val and tRNA Arg, a tRNA-unrelated region, and a poly-A tail. Analysis of the chromosomal distribution of ROn-1 and ROn-2 by fluorescent in situ hybridization showed that both SINE sequences are present in all chromosomes of tilapia, and organized in small clusters. The only exception was a large cluster of ROn-1 repeats found in the middle of the long arm of chromosome 1. In view of our data we discuss the hypothesis that the absence of large clusters of SINE sequences and the structural composition of these sequences may explain the absence of base-specific fluorochrome bands in the chromosomes of tilapia.
Keywords: Chromosome structure; Fish; Fluorescent in situ hybridization; Retrotransposon; SINE; Cichlidae; Oreochromis; Oreochromis niloticus; Tilapia; transposons